Spirit and psyche : a new paradigm for psychology, psychoanalysis, and psychotherapy - Schermer, Victor L. (Jessica Kingsley Publishers, 2003)
In recent years, there has been an increasing interest in linking depth psychology and psychotherapy with spirituality. This book explores the expanding literature on spirituality as an important dimension of psychology, and explains the relationship between psychological treatment and spiritual healing. The author examines ideas from religious traditions including Judeo-Christian, Hindu and Buddhist, and considers their implications for psychotherapy and personal growth. He discusses Jungian psychology, the later work of the psychoanalyst Bion - and how object relations theory connects with t.